ALTERNATIVE PRE-LAB ASSESSMENT FOR PRACTICAL CHEMISTRY COURSES IN PRE-UNIVERSITY: IMPLEMENTATION OF JOTTER BOOK - Ayu Afiqah Nasrullah; Sitty Nur Syafa Bakri; Mohd Azrul Abdul Rajak; Suriana Lasaraiya (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
The jotter book concept is not a novel method in scientific research. This practice is common not only among undergraduate students but also among postgraduate students, scientists, and researchers who use it to understand theories, concepts, and newly learned experimental procedures since it is important and significant pre-laboratory (pre-lab) preparation before an experiment is conducted. However, using a jotter book as one component of alternative pre-laboratory (pre-lab) assessment in assessing student achievement at pre-University level is something that has never been done before. In this paper, we proposed the rationale in implementation of the jotter book as one of the alternative assessments for the Chemistry course (SK0011-Practical Chemistry I and SK0021-Practical Chemistry II) for the foundation of science students in the Preparatory Centre for Science and Technology (PPST), Universiti Malaysia Sabah. Sample of 353 students from the intake session 2020/2021 are involved in this study. The improvement in the student grade from semester 1 to semester 2 will be discuss in this paper as the preliminary study.